MENGENAL MEDIASI SEBAGAI SALAH SATU CARA PENYELESAIAN SENGKETA - Siti Nur Azizah; Wagiman; Adrian Bima Putra (LPPM Universitas Ekasakti, 2024)
Mediation is increasingly popular. As a result, slowly but surely, people are starting to look at Alternative Dispute Resolution, which basically allows the parties to choose the forums they agree on. The phenomenon of using Alternative mechanisms is strengthening. Alternative Dispute Resolution (APS) is seen as an integral part of the business itself and is considered suitable for the business world because the resolution is fast and cheap. Dispute resolution as mediation has been known since the beginning in Indonesia because the customary system in resolving cases always upholds deliberation and consensus through traditional forums in each region in Indonesia. As time goes by, this is enforced in court (Mediation-Linked Court) as a form of legal justice. However, the mediation process in court must be enforced through the settlement of civil settlements. If mediation as regulated in Supreme Court Regulation Number 1 of 2016, if mediation is not carried out, the judgment will be abolished for legal purposes.